Human introduction or natural dispersion? Atlantic Ocean occurrence of the Indo-Pacific whitetip reef shark Triaenodon obesus - Bornatowski, H.; Loose, R.; Sampaio, C. L.S.; Gadig, O. B.F. [UNESP]; Carvalho-Filho, A.; Domingues, R. R. [UNESP] (Wiley, 2018)
Occurrence of multiple whitetip reef sharks Triaenodon obesus in the Atlantic Ocean is reported for the first time from near a sunken ferry off the Paraná coast in south-eastern Brazil. This occurrence is hypothesized to have been caused by either a human introduction or a remarkably long oceanic displacement.
Keywords: elasmobranch; migration; new record; non-indigenous species; Triaenodon obesus